STUDY OF BANK CAPACITOR NEEDS ANALYSIS OF POWER FACTOR IMPROVEMENT IN THE WATER INTAKE UNIT OF PT PUPUK ISKANDAR MUDA (PT PIM) - Hari Bukti; Hamdani Hamdani; Siti Anisah (Sean Institute, 2022)
The used of an electric motor which is an inductive load will cause reactive power which can reduce the value of the power factor. This can have an impact on increasing the electric power bills charged to users due to the kVar pinalty given by PT PLN (Persero) as a power supplier company. This paper aims to analyze the need for a capacitor bank to improve the power factor of the PT PIM water intake unit. Based on the results of data analysis that has been carried out, it is found that the value of the power factor (Cosφ1) at the Water Intake Unit of PT PIM for the last six months has an average value of 0.76 so that a reactive power compensator from a capacitor bank of 154 kVar is needed to achieve a power factor of 0.85